2020
DOI: 10.1177/0022219420914551
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Students Identified With Dyslexia Within the Context of State Legislation

Abstract: All but seven U.S. states have laws that govern some aspects of dyslexia screening, intervention, or teacher training in public schools. However, in the three states that mandate child-level reporting, data indicate lower than expected rates of dyslexia identification when compared with commonly accepted dyslexia prevalence rates. To better understand this apparent mismatch, this study explores factors that might predict the school-assigned identification of individuals with dyslexia. Deidentified data on 7,94… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 31 publications
(41 reference statements)
1
25
0
Order By: Relevance
“…Because findings of disability under-identification have been repeatedly replicated (e.g., Farkas et al, 2020; Morgan et al, 2015, 2017; Odegard et al, 2020) and, as indicated here, are largely robust to the possibility of unmeasured confounding, federal law and regulation may need to be redirected to instead monitor for systemic bias resulting in disability under-identification for students who are Black or Hispanic (Morgan et al, 2015, 2017). A recently proposed way to do so would for U.S. school districts to adjust the reported RRs for achievement gaps (Farkas et al, 2020; Morgan et al, 2017).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Because findings of disability under-identification have been repeatedly replicated (e.g., Farkas et al, 2020; Morgan et al, 2015, 2017; Odegard et al, 2020) and, as indicated here, are largely robust to the possibility of unmeasured confounding, federal law and regulation may need to be redirected to instead monitor for systemic bias resulting in disability under-identification for students who are Black or Hispanic (Morgan et al, 2015, 2017). A recently proposed way to do so would for U.S. school districts to adjust the reported RRs for achievement gaps (Farkas et al, 2020; Morgan et al, 2017).…”
Section: Discussionmentioning
confidence: 80%
“…Measured confounds included the district’s Black- or Hispanic-White achievement gaps, enrollment size, percentage of students receiving free or reduced-price lunch, and the percentage of Black or Hispanic students as well as state fixed effects. Study 3 (i.e., Odegard et al, 2020) reported ORs for learning disabilities in reading based on analyses of student-level data from 7,947 second graders from a U.S. state. Measured confounds included student-level reading achievement, biological sex, and eligibility for free or reduced-price lunch as well as school-level factors including racial, ethnic, or economic composition.…”
Section: Methodsmentioning
confidence: 99%
“…Some have suggested that unexpectedness might be signaled by economic or environmental factors (Hammill & Allen, 2020). There are serious risks for equity here, of course, as the subjectivity involved in any decision making that is conditioned by perceptions of students’ home and neighborhood environments will work against the interests of those who are socially and economically disadvantaged or from minority backgrounds (Chapman & Tunmer, 2019; Odegard, Farris, Middleton, Oslund, & Rimrodt‐Frierson, 2020; Rutter, 1978).…”
Section: How Is the Term Dyslexia Understood?mentioning
confidence: 99%
“…A dyslexia 3 (persistent intractability to high‐quality intervention) conception brings its own problems of measurement and operationalization (Odegard et al, 2020). Having identified such students, it is unclear how extensive a period of failure to improve one’s reading skills would be necessary before a diagnosis could be made.…”
Section: How Is the Term Dyslexia Understood?mentioning
confidence: 99%
“…To date, 43 U.S. states have dyslexia laws, and a growing number of states have initiatives and resolutions to promote dyslexia awareness in K12 settings (National Center on Improving Literacy, 2019), including dyslexia screening (Youman and Mather, 2018). Most U.S. states have laws governing dyslexia screening, intervention, or professional development; however, no research exists on connections between these initiatives and improved dyslexia identification or intervention outcomes (Phillips and Odegard, 2017;Odegard et al, 2020).…”
Section: Legislation Supporting School Professionals' Dyslexia Knowledgementioning
confidence: 99%